1999
DOI: 10.7601/mez.50.9_1
|View full text |Cite
|
Sign up to set email alerts
|

The geographical distribution of vectors of Chagas' disease and populations at risk of infection in Guatemala

Abstract: The fauna and the geographical distribution of vectors of Chagas' disease were investigated based on the man-hour collection, from mud walls or palm-thatched houses in 236 villages, from the year 1995 through 1997, throughout Guaternala. A total of 1,131 vectors cornprising 731 (64,6%) of Triatoma dimidiata, 53 (4,7%) of Tl nitida and 347 (30,7%) ofRhodniusProlixus were found. 71 dimidiata was collected in 16 eut of 22 departments, whereas R. Prolixus was collected in five departments, and T nitida was collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 2 publications
1
57
1
4
Order By: Relevance
“…nitida was previously reported in Guatemala in the departments of Baja Verapaz, Alta Verapaz, Chiquimula, Jalapa and Guatemala (Peñalver 1953, Tabaru et al 1999. This is the first report of the presence of this species in the departments of Huehuetenango, Jutiapa, Quiche and Santa Rosa.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…nitida was previously reported in Guatemala in the departments of Baja Verapaz, Alta Verapaz, Chiquimula, Jalapa and Guatemala (Peñalver 1953, Tabaru et al 1999. This is the first report of the presence of this species in the departments of Huehuetenango, Jutiapa, Quiche and Santa Rosa.…”
Section: Discussionmentioning
confidence: 67%
“…Peñalver (1953) included T. nitida together with T. dimidiata and Rhodnius prolixus, as the main vectors of Chagas disease in the country. A recent study reported the presence of T. nitida from inside houses (Tabaru et al 1999). However, the real vectorial importance of this species in Guatemala has not been established.…”
Section: Geographic Distribution and Morphometric Differentiation Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…This would contribute to genetic variation within the populations of this vector. These results also suggest the existence of migration, which would explain the high rates of reinfestation found after fumigation of houses (Tabaru et al 1999). Migration makes difficult the development of effective vector control strategies.…”
mentioning
confidence: 68%
“…While the domestic species R. prolixus has been reported to support higher transmission rates to humans and is therefore considered to be a more important disease vector (Ponce, 1999;Tabaru et al, 1999), T. dimidiata is a much greater challenge to control because of its adaptation to both domestic and peri-domestic habitats. Vector control programs in South America have proven highly successful at reducing both home infestation rates and the incidence of new infections in affected areas (Schmunis et al, 1996).…”
Section: Introductionmentioning
confidence: 99%